Role of Follicle-Stimulating Hormone in Spermatogenesis - Oduwole, Olayiwola O.; Peltoketo, Hellevi; Huhtaniemi, Ilpo T. (Frontiers in Endocrinology, 2018)
Spermatogenesis is a concerted sequence of events during maturation of spermatogonia into spermatozoa. The process involves differential gene-expression and cell-cell interplay regulated by the key endocrine stimuli, i.e., follicle-stimulating hormone (FSH) and luteinizing hormone (LH)-stimulated testosterone. FSH affects independently and in concert with testosterone, the proliferation, maturation and function of the supporting Sertoli cells that produce regulatory signals and nutrients for the maintenance of developing germ cells. Rodents are able to complete spermatogenesis without FSH stimulus, but its deficiency significantly decreases sperm quantity. Men carrying loss-of-function mutation in the gene encoding the ligand (FSHB) or its receptor (FSHR) present, respectively, with azoospermia or suppressed spermatogenesis. Recently, the importance of high intratesticular testosterone concentration for spermatogenesis has been questioned. It was established that it can be completed at minimal intratesticular concentration of the hormone. Furthermore, we recently demonstrated that very robust constitutive FSHR action can rescue spermatogenesis and fertility of mice even when the testosterone stimulus is completely blocked. The clinical relevance of these findings concerns a new strategy of high-dose FSH in treatment of spermatogenic failure.